Microencapsulação e avaliação da estabilidade do corante natural extraído da casca da jabuticaba (Myrciaria spp.) para aplicação em alimentos - Ferracini, Luana dos Anjos (2015)
The jabuticaba is the fruit from the “jabuticabeira” tree, which belongs to the Myrtaceae Family. This species of fruit is widely spread throughout Brazil. The peel from the jabuticaba fruit (Myrciaria spp.) has several nutritional benefits due to the high levels of phenolic and other bioactive compounds found in it. Its antioxidant activity, also important for nutritional purposes, is due mainly to the presence of anthocyanins. Antioxidants are widely used in foods as natural deterrents of spoilage due to aging and oxidative processes. These compounds, that also naturally occur in all living organisms, are responsible for the reduction of oxidative effects produced by free radicals. The aim of the present work was to encapsulate and characterize the dye extracted from the jabuticaba peel, in order to use it as a natural and functional dye in foods. The jabuticaba peel extract was further encapsulated with maltodextrins and gum Arabic with the use of a spray dryer. The levels of anthocyanins, total phenolic compounds and antioxidants was monitored throughout the 7 days of storage. The liquid extract, without encapsulation, was used as a control. When compared to the wet extract, all levels of anthocyanins, phenolic compounds, flavonoids and antioxidant activity dropped. This suggests that these compounds degraded after drying and also that the degradation was not reduced by the encapsulating agent.